Menusantarakan Al-Quran: Mengembalikan Kegemilangan Budaya Kerukunan Antar Umat Beragama - Lufaefi, Lufaefi (Jurnal Al-Ashlah, 2017)
English :Diversity is a fact that is often denied by some who do not want to be responsible, so often assume others who disagree and not the same as himself as the culprit of mistakes, and he is the most correct among others. They forget the history of the plurality of the country. This has actually hurt the already grounded culture in the archipelago that this nation was born into a culture of diversity. Unfortunately, the person who is reluctant to take responsibility often makes the verses of the Quran justify his behavior. Consequently, the Quran is often politicized for the benefit of the individual, or even his group by putting aside the cultural heritage mentioned above. Yet the essence of holy revelation (al-Quran) always tells us to uphold the truth in diversity culture. The culture of multiculturalism is indeed embodied and legalized in the Quran. This is in accordance with the mission of the Koran itself as a revelation that saalih likulli time wa al-meal that has long confirmed the legality of difference and diversity.Keywords: Diversity, Culture, Plurality.Â Indonesia:Keberagaman merupakan fakta yang sering dinafikan oleh sebagian orang yang tidak mau bertanggung jawab, sehingga sering kali menganggap orang lain yang tidak sepaham dan tidak sama dengan dirinya sebagai biang kesalahan, dan dirinyalah yang paling benar diantara yang lain. Mereka melupakan sejarah kemajemukan negeri ini. Hal ini sejatinya telah mencederai budaya yang sudah membumi di nusantara bahwa bangsa ini terlahir atas budaya keberagaman. Sayangnya, orang yang enggan untuk bertanggung jawab tersebut sering menjadikan ayat Al-Quran sebagai justifikasi kelakuannya itu. Akibatnya al-Quran sering dipolitisasi demi kepentingan pribadi, atau bahkan kelompoknya dengan mengesampingkan warisan budaya tersebut di atas. Padahal hakikatnya wahyu suci (al-Quran) selalu menyuruh kita untuk menegakkan kebenaran dalam budaya keberagaman. Budaya multikulturalisme sungguh termaktub dan dilegalkan di dalam al-Quran. Hal ini sesuai dengan misi al-Quran itu sendiri sebagai wahyu yang saalih likulli zaman wa al-makan yang telah sejak lama mengkonfirmasi akan legalitas perbedaan dan keberagaman.Kata Kunci: Keberagaman, Budaya, Pluralitas.